(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Keywords: In Vitro; cloning; Withania sp.; NAA (Naphthaleneacetic acid); BAP (benzyl amino purine); MS (Murashige & Skoog); GA (Gibberelic acid). Bangladesh j. genet. biotechnol. 7 (1&2): 75-77, 2006 (June & December)